MYB10 plays a major role in the regulation of flavonoid/phenylpropanoid metabolism during ripening of Fragaria x ananassa fruits - Medina-Puche, Laura (Journal of experimental botany, 2014)
This work characterized the role of the R2R3-MYB10 transcription factor (TF) in strawberry fruit ripening. The expression of this TF takes place mainly in the fruit receptacle and is repressed by auxins and activated by abscisic acid (ABA), in parallel to the ripening process. Anthocyanin was not produced when FaMYB10 expression was transiently silenced in fruit receptacles. An increase in FaMYB10 expression was observed in water-stressed fruits, which was accompanied by an increase in both ABA and anthocyanin content. High-throughput transcriptomic analyses performed in fruits with downregulated FaMYB10 expression indicated that this TF regulates the expression of most of the Early-regulated Biosynthesis Genes (EBGs) and the Late-regulated Biosynthesis Genes (LBGs) genes involved in anthocyanin production in ripened fruit receptacles. Besides, the expression of FaMYB10 was not regulated by FaMYB1 and vice versa. Taken together, all these data clearly indicate that the Fragaria × ananassa MYB10 TF plays a general regulatory role in the flavonoid/phenylpropanoid pathway during the ripening of strawberry